2016
DOI: 10.5539/ies.v9n10p34
|View full text |Cite
|
Sign up to set email alerts
|

Development of Program to Enhance Strategic Leadership of Secondary School Administrators

Abstract: This research aimed to 1) study principles, attributes and skills needed for secondary school administrators, 2) investigate current situations, desirable conditions and needs for strategic secondary school administrators, 3) develop a strategic secondary school administrator enhancement program, and 4) explore the efficiency level of the strategic secondary school administrator enhancement program by using the developmental research process. Sampling and data collection were as follows: step one, collect data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…From our findings, it appears that this issue is being little explored. Despite the important contributions of authors cited in this scoping review (Aydin et al, 2015;Chatchawaphun et al, 2016;Prasertcharoensuk and Tang, 2017;Ali, 2018;Chan, 2018;Ismail et al, 2018;Khumalo, 2018), minor advances seem to have been made after 2010. This is intriguing taking into account the leaders' role in the third wave of educational reform, where strategic leadership pursues a new vision and new aims for education due to maximizing learning opportunities for students through "triplisation in education' (i.e., as an integrative process of globalization, localization and individualization in education)" (Cheng, 2010, p. 48).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…From our findings, it appears that this issue is being little explored. Despite the important contributions of authors cited in this scoping review (Aydin et al, 2015;Chatchawaphun et al, 2016;Prasertcharoensuk and Tang, 2017;Ali, 2018;Chan, 2018;Ismail et al, 2018;Khumalo, 2018), minor advances seem to have been made after 2010. This is intriguing taking into account the leaders' role in the third wave of educational reform, where strategic leadership pursues a new vision and new aims for education due to maximizing learning opportunities for students through "triplisation in education' (i.e., as an integrative process of globalization, localization and individualization in education)" (Cheng, 2010, p. 48).…”
Section: Discussionmentioning
confidence: 96%
“…Other studies were also focused on the characteristics of strategic leadership with different populations and countries. Chatchawaphun et al (2016) identified the principles, attributes, and skills of the strategic leadership of secondary school administrators from Thailand. The principles identified within the sample of principals included appropriate values, modern visionary, future focusing strategy, empirical evidence focus, intention toward accomplishment, decency, and making relationships.…”
Section: How Should Strategy and Strategicmentioning
confidence: 99%
See 1 more Smart Citation
“…The elements of the program consisted of rationale, objectives, contents, procedures, and evaluations (Khakhlong, 2013;Pimko, 2014;Songboonsart, 2016;Chatchawaphun et al, 2016;Kunpadi, 2016;Chalorcharoenying, 2016;Jungsuttiwong, 2020) The procedures for developing a program included studying and analyzing the need for the program, creating the program, implementing the program, and evaluating the program (Noppakun, 2005;Barr & Keating, 1990;Boone, 1992;Knowles, 1980;Style, 1990;Houle, 1996).…”
Section: Theoretical Conceptual Frameworkmentioning
confidence: 99%
“…Di dalam standar ini, kriteria yang diharapkan dapat dipenuhi oleh kepala sekolah adalah dengan memfasilitasi pengembangan, pelaksanaan dan pengelolaan visi pembelajaran kepada seluruh warga sekolah. Kepemimpinan Strategis mengacu kepada penerapan prinsip, pengetahuan dan keterampilan kepala sekolah untuk menciptakan, memelihara, mengembangkan dan mengartikulasikan visi dan tujuan sekolah sehingga mampu membawa sekolah kepada perubahanperubahanyang lebih baik (Chatchawaphun et al, 2016;Priansa, 2017;Deeboonmee, 2014). Indikator kepemimpinan instruksional sekolah antara lain; memperhatikan visi, misi, nilai-nilai, dan tujuan sekolah; mengimplementasikan kebijakan pemerintah; menentukan tujuan dan ekspektasi yang dipenuhi siswa dan meningkatkan mutu kepemimpinan.…”
Section: ) Kepemimpinan Strategisunclassified